Trace element partitioning during incipient melting of phlogopite-peridotite in the spinel and garnet stability fields. (15th June 2022) - Condamine, Pierre; Couzinié, Simon; Fabbrizio, Alessandro; Devidal, Jean-Luc; Médard, Etienne
Abstract: Potassium-rich magmatism represents subordinate magma volumes worldwide but has been observed in many geodynamic settings. Most potassic magmas are thought to derive from very-low degrees of melting of metasomatized mantle lithologies. We performed piston-cylinder experiments to determine trace element partition coefficients between incipient potassic silicate melts and phlogopite ± pargasite peridotite in the spinel (1 GPa) and garnet stability fields (3 GPa). Most of the rare Earth elements (REEs) are compatible in pargasite but incompatible in phlogopite. Although garnet remains the mineral phase most efficiently fractionating heavy from light REEs ( D Yb grt / m e l t / D La grt / m e l t > 750), orthopyroxene can also significantly fractionate REEs, e.g., achieving D Yb opx / m e l t / D La opx / m e l t > 100 at 3 GPa. Mineral-liquid partition coefficients vary by about one order of magnitude between incipient melts derived from the spinel and garnet stability fields. We thus show that trace element partitioning at the onset of melting is controlled more by pressure (through melt composition) than by the extent of melting. With increasing pressure, Rb and Ba exhibit different behaviors in phlogopite, with D Ba phl / m e l t > D Rb phl / m e l t at 1 GPa and the opposite at 3 GPa. At 1 GPa, a decrease of melt polymerization (lower NBO/T) with increasing melt fraction translates into a significant decrease of most phlogopite partition coefficients. Finally, we show that resolvable inter-element fractionations do occur when phlogopite- (and pargasite)-bearing peridotite are melted, indicating that trace element ratios are not always faithfully representative of that of their sources but bear the imprint of varied P–T conditions of melting and contrasted pre-metasomatic histories. This self-consistent partition coefficient dataset thus gives a new scope to understand the complex petrogenesis of K-rich magmas in orogenic settings.